2022
DOI: 10.1111/1365-2664.14109
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen‐mediated selection and management implications for white‐tailed deer exposed to chronic wasting disease

Abstract: 1. Pathogens can cause host extinction, affect population dynamics and influence natural selection. Host susceptibility to pathogens can vary by species, demographics and genetics which affect epizootic and population dynamics, ultimately determining population trends and evolution.2. Chronic wasting disease (CWD), a fatal neuro-degenerative prion disease of cervids, has varying host susceptibility conferred by polymorphisms of the prion protein gene (PRNP) at codon 96 for white-tailed deer Odocoileus virginia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 119 publications
(232 reference statements)
2
13
0
Order By: Relevance
“…For example, Rogers et al (2022) suggested that increased harvest of males could be effective at reducing epidemics when high CWD prevalence in males was caused by high male-to-male transmission of prions. Similarly, Ketz et al (2021) found higher susceptibility and prevalence of CWD in males and that increased harvest of male WTD could reduce the prevalence of CWD.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, Rogers et al (2022) suggested that increased harvest of males could be effective at reducing epidemics when high CWD prevalence in males was caused by high male-to-male transmission of prions. Similarly, Ketz et al (2021) found higher susceptibility and prevalence of CWD in males and that increased harvest of male WTD could reduce the prevalence of CWD.…”
Section: Discussionmentioning
confidence: 88%
“…For example, Rogers et al (2022) suggested that increased harvest of males could be effective at reducing epidemics when high CWD prevalence in males was caused by high male‐to‐male transmission of prions. Similarly, Ketz et al (2021) found higher susceptibility and prevalence of CWD in males and that increased harvest of male WTD could reduce the prevalence of CWD. Here, we highlight the potential for elevated male‐to‐male transmission through indirect contact at scrapes; therefore, scrapes deserve more attention for research and management strategies.…”
Section: Discussionmentioning
confidence: 89%
“…The estimated rate of spread also provides a potential guideline for conducting monitoring in surrounding areas to detect disease spread. Increased genetic selection pressure on males and females favors a higher frequency of less susceptible deer, depending on genetically neutral hunting pressure (Ketz et al, 2022). The increasing potential for environmental prion contamination could provide a long-term source of infection exceeding that from direct contact with CWD+ deer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found that increased harvest of male mule deer can lead to reduction in CWD prevalence and management actions promoting an abundance of mature male deer likely contribute to rapid growth of CWD prevalence (Conner et al, 2021;Miller et al, 2020) and higher transmission rates in males. A better understanding of male transmission would be beneficial to the development of alternatives to current CWD management recommendations focused on reducing male abundance to reduce CWD prevalence and transmission (Jennelle et al, 2014;Ketz et al, 2019Ketz et al, , 2022Miller et al, 2020;Samuel & Storm, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation